World Bank agricultural investments for improved climate change resilience in the ag sector and reduced contributions to GHG emissions rise from 28% (2016) to 45% (2018) of committed budgets of new agriculture projects - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Three years ago, a CCAFS researcher was embedded within the agriculture group at WBG headquarters. The role of the researcher has been to strengthen the linkages and collaborative actions between the WBG and CGIAR, resulting in the following outcomes as reported by high-level Bank officials to an independent consultant (see Ref 1). - (1) Teams in the Agriculture Global Practice which design agricultural projects and programs; (2) plus governments/local partners–incorporating activities addressing climate change challenges; (3) behavioral change in many WB (low-income) country clients/governments towards adoption of CSA approaches, policies, actions; (4) Directors and regional managers at WB incorporating climate smart approaches and the scientific evidence base supporting them as part of their corporate strategy and in international climate and food system negotiations.